Apparent density, trypanosome infection rates and host preference of tsetse flies in the sleeping sickness endemic focus of northwestern Uganda - Opiro, R.; Opoke, R.; Angwech, H.; Nakafu, E.; Oloya, F.A.; Openy, G.; Njahira, Moses; Macharia, Mercy; Echodu, R.; Malinga, Geoffrey Maxwell; Opiyo, E.A. (Springer, 2021)
Background